Surface Display of Peptides Corresponding to the Heptad Repeat 2 Domain of the Feline Enteric Coronavirus Spike Protein on Bacillus subtilis Spores Elicits Protective Immune Responses Against Homologous Infection in a Feline Aminopeptidase-N-Transduced Mouse Model - Chen, Chu; Li, Ya-Li; Lv, Fang-Li; Xu, Ling-Dong; Huang, Yao-Wei (Frontiers in Immunology, 2022)
Although feline coronavirus (FCoV) infection is extremely common in cats, there are currently few effective treatments. A peptide derived from the heptad repeat 2 (HR2) domain of the coronavirus (CoV) spike protein has shown effective for inhibition of various human and animal CoVs in vitro, but further use of FCoV-HR2 in vivo has been limited by a lack of practical delivery vectors and small animal infection model. In order to overcome these technical challenges, we first constructed a recombinant Bacillus subtilis (rBSCotB-HR2P) expressing spore coat protein B (CotB) fused to an HR2-derived peptide (HR2P) from a serotype II feline enteric CoV (FECV). Immunogenic capacity was evaluated in mice after intragastric or intranasal administration, showing that recombinant spores could trigger strong specific cellular and humoral immune responses. Furthermore, we developed a novel mouse model for FECV infection by transduction with its primary receptor (feline aminopeptidase N) using an E1/E3-deleted adenovirus type 5 vector. This model can be used to study antiviral immune response and evaluate vaccines or drugs, and is an applicable choice to replace cats for the study of FECV. Oral administration of rBSCotB-HR2P in this mouse model effectively protected against FECV challenge and significantly reduced pathology in the digestive tract. Owing to its safety, low cost and probiotic features, rBSCotB-HR2P is a promising oral vaccine candidate for use against FECV/FCoV infection in cats.